ANALYSIS OF INDICATIONS OF FINANCIAL STATEMENT FRAUD IN TECHNOLOGY COMPANIES IN INDONESIA USING THE FRAUD PENTAGON THEORY - Sely Cahyani Agustina Siahaan; I Ketut Sujana (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
Financial statements often become objects of financial fraud. The driving factors of financial statement fraud are pressure, opportunity, rationalization, capability, and arrogance, which are known as the fraud pentagon. The purpose of this study is to obtain empirical evidence of the effect of the fraud pentagon on financial statement fraud. The sample was selected using purposive sampling from 2021–2024, resulting in 68 observations. The data analysis technique used panel data regression. The results of the analysis show that financial stability, financial target, ineffective monitoring, and change in auditor have no effect on financial statement fraud. Meanwhile, nature of industry, change in director, and the frequent number of the CEO’s picture have a positive effect on financial statement fraud. The results of this study support agency theory, which explains the existence of differences in interests between principals and agents, thereby potentially giving rise to fraudulent behavior.